SQL Server on Azure Virtual Machines : A hands-on guide to provisioning Microsoft SQL Server on Azure VMs /: A hands-on guide to provisioning Microsoft SQL Server on Azure VMs. (2020) - D'Antoni, Joey; Davidson, Louis; Hirt, Allan; Martin, John; Nocentino, Anthony; Radney, Tim; West, Randolph
No abstract available